Valvotomy in calcific mitral stenosis - Smith, G. H. (1970)
The results of transventricular mitral valvotomy in 50 cases of heavily calcified mitral stenosis are presented. The mortality and quality of results in patients undergoing a first valvotomy were more satisfactory than in patients undergoing a second operation. Associated mitral incompetence has an adverse effect on the results, particularly after a second operation. As a result, it is suggested that closed valvotomy, in these circumstances, is only acceptable for patients who are undergoing a first operation and who have minimal or no regurgitation. Valve replacement is advised for all other cases.